Thyroid Hormone Receptor Mutations in Cancer and Resistance to Thyroid Hormone: Perspective and Prognosis. (8th June 2011) - Rosen, Meghan D.; Privalsky, Martin L.
Abstract : Thyroid hormone, operating through its receptors, plays crucial roles in the control of normal human physiology and development; deviations from the norm can give rise to disease. Clinical endocrinologists often must confront and correct the consequences of inappropriately high or low thyroid hormone synthesis. Although more rare, disruptions in thyroid hormone endocrinology due to aberrations in the receptor also have severe medical consequences. This review will focus on the afflictions that are caused by, or are closely associated with, mutated thyroid hormone receptors. These include Resistance to Thyroid Hormone Syndrome, erythroleukemia, hepatocellular carcinoma, renal clear cell carcinoma, and thyroid cancer. We will describe current views on the molecular bases of these diseases, and what distinguishes the neoplastic from the non-neoplastic. We will also touch on studies that implicate alterations in receptor expression, and thyroid hormone levels, in certain oncogenic processes.